Feasibility of RACT for 3D dose measurement and range verification in a water phantom. Issue 2 (26th January 2015) - Alsanea, Fahed; Moskvin, Vadim; Stantz, Keith M.
Abstract : Purpose: The objective of this study is to establish the feasibility of using radiation‐induced acoustics to measure the range and Bragg peak dose from a pulsed proton beam. Simulation studies implementing a prototype scanner design based on computed tomographic methods were performed to investigate the sensitivity to proton range and integral dose. Methods: Derived from thermodynamic wave equation, the pressure signals generated from the dose deposited from a pulsed proton beam with a 1 cm lateral beam width and a range of 16, 20, and 27 cm in water using Monte Carlo methods were simulated. The resulting dosimetric images were reconstructed implementing a 3D filtered backprojection algorithm and the pressure signals acquired from a 71‐transducer array with a cylindrical geometry (30 × 40 cm) rotated over 2 π about its central axis. Dependencies on the detector bandwidth and proton beam pulse width were performed, after which, different noise levels were added to the detector signals (using 1 μ s pulse width and a 0.5 MHz cutoff frequency/hydrophone) to investigate the statistical and systematic errors in the proton range (at 20 cm) and Bragg peak dose (of 1 cGy). Results: The reconstructed radioacoustic computed tomographic image intensity was shown to be linearly correlated to the dose within the Bragg peak. And, based on noise dependent studies, a detector sensitivity of 38 mPa was necessary to determine the proton range to within 1.0 mm (full‐width at half‐maximum) (systematic error < 150 μm) for a 1 cGy Bragg peak dose, where the integral dose within the Bragg peak was measured to within 2%. For existing hydrophone detector sensitivities, a Bragg peak dose of 1.6 cGy is possible. Conclusions: This study demonstrates that computed tomographic scanner based on ionizing radiation‐induced acoustics can be used to verify dose distribution and proton range with centi‐Gray sensitivity. Realizing this technology into the clinic has the potential to significantly impact beam commissioning, treatment verification during particle beam therapy and image guided techniques.